INOVASI PENGELOLAAN ZAKAT DAN WAKAF - Nuroini, Dina Afifah; Setiyawati , Putri Sulis; Umah , Shoffi Rohmatul; Wasifaul Qolbi, Syahroni; Latifah, Eny (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
The purpose of this research is to determine innovations in zakat and waqf management. The research method used is a library method by combining data sources from books and the results of previous research reports. The results of this research are that we can find out what innovations have developed in the management of zakat and waqf assets. First: zakat waqf assets can be managed through currently developing digital platforms. Second: zakat and waqf assets can be managed productively, where these assets are not only given freely to those who are entitled to them, but can be used as business or commercial capital to make them productive.